PERANCANGAN SISTEM INFORMASI PELAYANAN IMUNISASI BAYI DI PUSKESMAS SAWAH LEBAR BENGKULU - Endah Dwi Lestari; Putri Dwi Susanti (Jurnal Infokes, 2021)
The research aimed to know the information system design baby immunization services using microsoft visual studio 2010 at Puskesmas Sawah Lebar Bengkulu. The research method was the qualitative method in descriptive approach with waterfall development method. Data collection techniques was used by observation, interview and completed with a literate study which had relation with the main issues. The problem that were found from the research are: (1) the time required by employees is long enough, because the problem that often occur on the system; (2) there was no computerized system of Baby Immunization services Information which better; (3) preparing activity Baby Immunization Services Information system reports hampered because the program is not working properly.The suggestion given were by : (1) Designing the Baby Immunization Services Information system to improve the quality of health services; (2) Need an better application that can supports the process of Baby Immunization Services Information system and facilitate the process of manufacture Maternal And Child Health Services Information system; (3) Evaluated the Baby Immunization Services Information system so that employees know their duties and obligations in completing the report of . Keywords : Design, Information system ,Baby Immunization service, Microsoft Visual Studio 2010